Socio-sartorial inscriptions of social class in a study of school and identity in Ireland. Issue 3 (4th May 2019) - Cahill, Kevin
ABSTRACT: This paper explores how classed identities are constituted through the socio-sartorial inscriptions of a working-class school and community in an Irish city in the twenty-first century. The data of the paper were generated through a wider three-year critical ethnography of a school community. The focus here is upon the identity work of the participants as it is connected to the school and the wider community. The article makes a particular contribution to the conversation of cultural constructions of class; in this instance through socio-sartorialism and how cultural capital is embodied and performed through people. The paper offers illustrative cases formed from participant interviews and an analysis of how socio-sartorial inscription contributes to the making of class in educational contexts.